Exploring the Root Cause of Quiet Quitting Phenomena Among Gen-Z: A Systematic Literature Review of Contributing Factors - Dika Lesmana, Anak Agung Bagus; Yunita, Putu Irma (Syntax Corporation, 2025)
The phenomenon of quiet quitting has become a global concern, representing a decline in work engagement, particularly among Generation Z. This literature review aims to analyze the factors influencing the emergence of quiet quitting and to explore strategies for addressing it, drawing on findings from various international studies. This study employs a narrative review method, utilizing PubMed, Elsevier, and Google Scholar as databases to identify relevant articles. The keywords used are